The outcomes of a toxic work environment on employee engagement. The boss approach as the moderating variable - Mdhlalose, Dickson (Journal of Management and Business Education, 2025)
In an environment at work characterized by toxicity, the absence of trust and support is evident among team members and management. The prevalence of backstabbing, gossip, and a blame culture may create challenges in fostering good relationships and promoting cooperation. This research examines the effects of a hostile work environment, namely the managerial approach of the boss, on employee engagement. This study adopted a theoretical philosophical approach, which emphasizes understanding the underlying principles and frameworks that influence the phenomena being investigated. An informal design was utilized to encourage a flexible and adaptive research process, enabling the exploration of nuances and variations within the data. This study utilized casual design (explanatory design) and secondary sources were used for this investigation. Secondary data was gathered through several internet search engines and specialized periodicals. To facilitate the inquiry, relevant books and articles were read. A positive correlation exists between the perceived level of toxicity in a leader and a toxic work environment, and the probability of employee disengagement. A work environment characterized by toxicity, including toxic leadership aspects, has a detrimental effect on employee engagement, leading to employees displaying aloofness and expressing a desire to depart from the organisation, and so contributing to an increase in the attrition rate. The presence of toxic leadership significantly impacts employees' emotional connections to their respective organisations. Inadequate levels of commitment within a manufacturing entity may lead to heightened rates of absenteeism and diminished production quantities because of insufficient workforce availability. Leaders should receive specialized training from organisations that emphasise toxic leadership, conflict resolution, constructive criticism, and emotional intelligence. By giving managers these abilities, they may lessen harmful behaviours and create a positive work atmosphere. The significance of this research study adds to the existing corpus of information about the effects of the toxic work environment boss approach on employee engagement. The scope of this investigation was restricted to the use of secondary data and the constrained availability of academic literature.